A comparative applicability study of model-fitting and model-free kinetic analysis approaches to non-isothermal pyrolysis of coal and agricultural residues. (15th March 2019) - Ashraf, Asma; Sattar, Hamed; Munir, Shahid
Highlights: Comparison of model-fitting and model-free methods for pyrolysis of coal and biomass. Model-fitting methods predicted lower values of E compared with model-free methods. The two model-fitting methods predicted different kinetic parameters from each other. Isoconversional models had high R 2 values and yielded more reliable results. Abstract: Comparative applicability of model-fitting and model-free kinetic methods to pyrolysis of two coals and four agricultural residues was analyzed by using two models from each class of methods. The two model-fitting methods were Arrhenius and Coats-Redfern while Friedman and Vyazovkin were selected from the model-free category. According to kinetic analysis by all four models, the fuels could be arranged in following order of activation energy, CC > DC > SD > RH > FS > CH. The two model-fitting methods exhibited different kinetic parameters (E and reaction mechanism). All fuels were found to have a third order reaction mechanism (F3) by using Arrhenius model. In the case of Coats-Redfern model, the CC and RH displayed 3-dimensional diffusion mechanism (D3) whereas CH, SD and FS exhibited third order reaction mechanism (F3). DC was found to decompose according to 2-dimensional diffusion mechanism (D2). The percentage difference between the values of activation energy found from the Arrhenius and Coats-Redfern models was in the range of 6.24–21.64%. The percentage difference between the values of activation energy from two isoconversional models was not more than 3.29% for coals and 4.91% for agricultural residues in the fractional conversion range of 0.1–0.7. Isoconversional models were found to be more reliable and accurate for estimation of non-isothermal kinetics for pyrolysis of solid fuels compared with model-fitting methods.